2017
DOI: 10.5944/openpraxis.9.1.432
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Student and Faculty Perceptions of Textbook Costs in Higher Education

Abstract: The cost of textbooks has continued to impact students in higher education. Students have reported that they make decisions on which courses to take based on the specific cost of textbooks. Faculty have reported willingness to use open textbooks to help ease the burden on students but are unsure where to find viable options. We examined the responses of 676 students and 573 faculty from a large private university (Brigham Young University, Provo, Utah) to understand the real impact of textbooks costs to studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 7 publications
1
60
1
Order By: Relevance
“…Our study context differs from that described in the Senack (2014;Senack & Donoghue, 2016), Jhangiani and Jhangiani (2017) and the Martin et al (2017) studies. Our study was conducted on one campus of one institution in New Zealand.…”
Section: Design and Methodscontrasting
confidence: 39%
See 2 more Smart Citations
“…Our study context differs from that described in the Senack (2014;Senack & Donoghue, 2016), Jhangiani and Jhangiani (2017) and the Martin et al (2017) studies. Our study was conducted on one campus of one institution in New Zealand.…”
Section: Design and Methodscontrasting
confidence: 39%
“…Evidence from outside our context indicates that the cost of textbooks is having a negative effect on student behaviours (e.g., Martin, Belikov, Hilton, Wiley & Fischer, 2017;Jhangiani & Jhangiani, 2017;Senack & Donoghue, 2016). The problem is serious enough that it is not only influencing students' choice of courses but also their academic achievement (Hilton, 2016;Martin et al, 2017;Senack, 2014).…”
Section: Background To the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Resonating somewhat with the COUP framework, student costs, use, and impressions were reported, and faculty impressions of quality, student use, and, notably, opportunities provided by the open licensing for rethinking how they organize and teach the content. Martin, Belikov, Hilton, Wiley, D., and Fischer (2017) surveyed nearly 700 students and more than 550 faculty at a large private university (Brigham Young) to discover how both groups have responded to high textbook costs and their willingness to use OER. They found that two-thirds of BYU students reported not having purchased at least one textbook because of cost concerns, and that many of these students thought this choice negatively impacted their grades (Martin et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Martin, Belikov, Hilton, Wiley, D., and Fischer (2017) surveyed nearly 700 students and more than 550 faculty at a large private university (Brigham Young) to discover how both groups have responded to high textbook costs and their willingness to use OER. They found that two-thirds of BYU students reported not having purchased at least one textbook because of cost concerns, and that many of these students thought this choice negatively impacted their grades (Martin et al, 2017). These figures are largely similar to those found in a statewide survey in Florida (Florida Virtual Campus Office of Distance Learning & Student Services, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%